Effect of graphene addition on microstructure and mechanical properties of cast aluminium alloy composite - Mohammad Na’aim, Abd Rahim; Mohd Shukor, Salleh; Saifudin Hafiz, Yahaya; Subramonian, Sivarao; Liew, Pay Jun; Azrin Hani, Abdul Rashid; Syarifah Nur Aqida, Syed Ahmad; Al-Zubaidi, Salah Salman (Semarak Ilmu Publishing, 2024)
Aluminium-reinforced metal matrix composites (Al-MMCs) are highly desirable because of their low density, excellent corrosion resistance, high thermal and electrical conductivity, high strength, and stiffness. This research intends to improve the mechanical properties of Al-MMCs for lightweight automotive and aerospace applications. A Taguchi method with two parameters and four levels was used to determine the optimum amounts of graphene nanoplatelets (GNPs) (0.1, 0.25, 0.5, and 0.6 wt%) and stirring duration (1, 2, 4, and 8 minutes). GNPs were added to the molten aluminium alloys through the stir-casting process to enhance the mechanical properties of the Al-MMCs. The results revealed that the Al-MMCs with 0.25 wt% GNPs and 8 minutes of stirring time produced the highest value of hardness and tensile properties. Under these parameters, the microstructure changed from dendritic to rosette, which had a tremendous effect on the improvement of the mechanical properties. The Ultimate Tensile Strength (UTS) and Yield Strength (YS) of the samples were improved after T6 heat treatment with a value of 210.26 MPa and 145.31 MPa, respectively, and the hardness was 116 HV while the elongation to fracture was 4.89%.The results showed that the high GNP concentration improved the mechanical properties of the Al-MMCs.